The Narrative Analysis of Todorov Film Story of Dinda - Bernard Realino Danu Kristianto; Maria Carolina Itu Leba; Angela Merici Elvina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2022)
Various film themes adorn cinema screens and digital platforms, but the theme of romance is still in demand by the people of Indonesia. The success of the film Later Kita Stories About Today, which presented a spin-off of the story in the film Story of Kale, made the production team experiment with packaging the story from a different point of view, with a similar plot in the film Story of Dinda. This study discusses narrative analysis in the film Story of Dinda with the aim of revealing the narrative picture of the film Story of Dinda so as to obtain a description of the discourse in terms of language, text and visuals. Using Tzvetan Todorov's narrative analysis method, this study aims to reveal the storyline from balance, disturbance to ending balance. The results of this study reveal that the film Story of Dinda tries to provide a discourse on toxic relationships in the form of emotional abuse by presenting the main plot of the story, a scene that takes place only in one location in a conversation between characters. The flashback scene can be concluded as a minor plot that is inserted with the aim of adding dramatization to the story, but its existence does not have a significant dramatic impact, only as a sweetener for the story.